Development of a System Dynamics Model to Optimize Productivity and Cost Efficiency in Sustainable Agricultural Systems - Devi Rahmawati Putri, Devi Rahmawati Putri; Murnawan, Hery (Indonesian Journal of Engineering and Technology (INAJET), 2025)
Sustainable agricultural systems require efficient input management to achieve optimal results in both productivity and profitability. This study aims to develop a system dynamics model to explore strategies for increasing productivity and cost efficiency in sustainable agriculture. The research was conducted in Singkalan Village, Balongbendo District, Sidoarjo Regency using STELLA software to build a simulation model. This model captures the relationship between key variables, including the use of superior crop varieties and semi-organic fertilizer, rice and corn yields, operational costs, and farmer profits. Three management scenarios were tested: (1) increasing productivity through superior varieties, (2) reducing operational costs by applying semi-organic fertilizer by 25%, and (3) combining the two approaches. The simulation results show that the combination of scenarios provides the best results, with an increase in rice productivity of 3.96%, a reduction in operational costs of 16.29%, and a profit for rice farmers of 1.27%. These results highlight the effectiveness of the system dynamics approach in assessing input-based policy interventions and supporting sustainable profit-oriented decision making in agriculture. Keywords: cost efficiency, productivity, profitability, system dynamics